MARKET RESEARCH MARKET VETERINARY DRUGS AND VETERINARY PHARMACY - І. V. Bushueva (Zaporožskij Medicinskij Žurnal)
The article is an analysis of current market veterinary medicines, the features of the basic trend of globalization on the market of veterinary drugs, tendencies of the growth in turnover of drugs for veterinary medicine.